2002
DOI: 10.3727/000000002783985666
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of Immortalized Human Hepatocytes with p21 to Enhance Differentiated Phenotypes

Abstract: We previously constructed an immortal human hepatocyte line NKNT-3 with a simian virus 40 T antigen (SV40T) to develop cell-based biological therapies. p21 is a molecule that regulates the transition from the G 1 phase to the S phase of the cell cycle. Investigators have demonstrated that overexpression of p21 induces differentiation in various cell lines. In the current study we examined the effect of p21 on differentiated phenotypes of SV40T-immortalized NKNT-3 cells. A replication-deficient adenovirus vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In general, most of the generated hepatocyte-derived cell lines are not tumorigenic, but display reduced or only limited liver-specific functionality [7, 20, 102]. Taking into account that proliferation and differentiation are mutually exclusive in vitro, it has been shown that overexpression of the cdki, p21 and the use of conditional immortalization strategies can stimulate to some extent differentiation of the cells [6, 23, 84, 85, 102, 111, 116-120]. Other anti-dedifferentiation strategies developed to counteract the loss of functionality in primary hepatocyte cultures, including co-culture systems and overexpression of liver-specific genes have also proven usefull [121, 122].…”
Section: Hepatocyte Immortalization Strategiesmentioning
confidence: 99%
“…In general, most of the generated hepatocyte-derived cell lines are not tumorigenic, but display reduced or only limited liver-specific functionality [7, 20, 102]. Taking into account that proliferation and differentiation are mutually exclusive in vitro, it has been shown that overexpression of the cdki, p21 and the use of conditional immortalization strategies can stimulate to some extent differentiation of the cells [6, 23, 84, 85, 102, 111, 116-120]. Other anti-dedifferentiation strategies developed to counteract the loss of functionality in primary hepatocyte cultures, including co-culture systems and overexpression of liver-specific genes have also proven usefull [121, 122].…”
Section: Hepatocyte Immortalization Strategiesmentioning
confidence: 99%
“…Immunofluorescent staining for albumin was conducted with immortalized and reverted 16-T3 cells with a labeled anti-albumin antibody, as previously reported [19]. Staining with Oregon green phalloidin (Molecular Probes, Eugene, OR) and Hoechst dye (Sigma, Saint Louis, MI) was simultaneously performed for specific staining of actin filaments and nuclei, respectively.…”
Section: Evaluation Of Hepatocyte-specific Functionsmentioning
confidence: 99%
“…The cells were regularly detached with trypsin and the number of viable cells counted by trypan blue exclusion test. The cell cycle status of both 16-T3 and reverted cells was analyzed by flow cytometry, as previously reported [19].…”
Section: Growth Curves and Cell Cycle Analysismentioning
confidence: 99%
“…Chang et al [44] reported that a combination of HDAC and PPAR-gamma ligand therapy for non-small lung cancers led to an increase in p21, cyclin-dependent kinase inhibitor, compared to either therapy alone and was followed by the induction of differentiation. Kunieda et al [45] also reported that p21 was associated with cellular differentiation and senescence in immortalized hepatocytes and the induction of p21 results in the enhancement of albumin and P450 expression. The expression of p21 was up-regulated when terminal differentiation was observed coupled with cell cycle arrest [46][47][48].…”
Section: Discussionmentioning
confidence: 93%